PENGEMBANGAN DAYA TARIK WISATA BUDAYA DESA SLANGIT, CIREBON, JAWA BARAT - Barunawati, Altri Tiyar; Paturusi, Syamsul Alam (Jurnal Master Pariwisata (JUMPA); Volume 02, Nomor 02, Januari 2016DO - 10.24843/JUMPA.2016.v02.i02.p06)
Slangit is a village in Cirebon, West Java that has potentials to be used as a cultural tourist attraction. These potentials include tradition and custom ceremonies, traditional art of masks and mask performances. This article investigates the the development strategy of cultural attractions in the village of Slangit. Data collection are conducted by observation, in-depth interviews, and documentation. Data was analysed using a descriptive qualitative method and by using SWOT analysis. The result shows that the attempt to use arts potential as tourist attraction has been fairly developed by artists group but it is far from adequate because the lack of coordination between artists group and the authority responsible to promote culture and tourism. It is suggested that the government to work together with communities and artists to promote the village potentials as cultural tourism attractions both as away to preserve arts and to develop tourism as source of local economy.
Keywords: development, cultural tourism attraction, the village of Slangit